Effect of different body measurements on body weight in Ghungroo pigs - Banik, S; Naskar, S; Pankaj, P K; Sahoo, N R; Tamuli, M K; Das, A (The Indian Journal of Animal Sciences, 2012)
The present investigation was carried out to study the effect of different body measurement traits on pre-weaning body weight of 264 records of Ghungroo pigs maintained at the Institute Farm of National Research Centre on Pig, Guwahati, Assam by path analysis. The result showed that maximum variability in pre-weaning body weight was explained by height at fore leg (20.98%); followed by body length (19.50%), heart girth (6.60%) and paunch girth (5.80%). Though there is high correlation of height at hind leg with body weight, but its direct effect is negative. Effect of height at shoulder is also negligible. It was concluded from the present study, that among different body measurement traits to explain the pre-weaning body weight of Ghungroo pigs major importance is to be given to height at fore leg, body length, heart and paunch girth.